Rupture process and aftershock focal mechanisms of the 2022 M6.8 Luding earthquake in Sichuan - Zhigao Yang; Danqing Dai; Yong Zhang; Xuemei Zhang; Jie Liu (Earthquake Science, 2022)
According to the China Earthquake Networks Center, a strong earthquake of M6.8 occurred in Luding County, Ganzi Tibetan Autonomous Prefecture, Sichuan Province, China (102.08°E, 29.59°N), on September 5, 2022, with a focal depth of 16 km. Rapid determination of the source parameters of the earthquake sequence is vital for post-earthquake rescue, disaster assessment, and scientific research. Near-field seismic observations play a key role in the fast and reliable determination of earthquake source parameters. The numerous broadband seismic stations and strong-motion stations recently deployed by the National Earthquake Intensity Rapid Report and Early Warning project have provided valuable real-time near-field observation data. Using these near-field observations and conventional mid- and far-field seismic waveform records, we obtained the focal mechanism solutions of the mainshock and M ≥ 3.0 aftershocks through the waveform fitting method. We were further able to rapidly invert the rupture process of the mainshock. Based on the evaluation of the focal mechanism solution of the mainshock and the regional tectonic setting, we speculate that the Xianshuihe fault formed the seismogenic structure of the M6.8 strong earthquake. The aftershocks formed three spatially separated clusters with distinctly different focal mechanisms, reflecting the segmented nature of the Xianshuihe fault. As more high-frequency information has been applied in this study, the absolute location of the fault rupture is better constrained by the near-field strong-motion data. The rupture process of the mainshock correlates well with the spatial distribution of aftershocks, i.e., aftershock activities were relatively weak in the maximum slip area, and strong aftershock activities were distributed in the peripheral regions.